2018
DOI: 10.2147/cmar.s159561
|View full text |Cite
|
Sign up to set email alerts
|

Combined microwave ablation and minimally invasive open decompression for the management of thoracic metastasis in breast cancer

Abstract: ObjectiveThe incidence rate of thoracic metastasis from breast cancer is increasing. Microwave ablation is one type of clinical therapy used to treat metastatic spine disease, although it can cause protein denaturation and immediate cell death, and coagulative necrosis can occur. Minimally invasive open decompression is associated with lower rates of surgical complications in comparison to traditional open surgery. Therefore, it is an alternative therapeutic option for spinal metastases. This study aimed to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Recently, Cheng et al [34] have shown that ultrasound-guided percutaneous MWA has the advantages of being a real-time, convenient, lower-cost and nonradiative treatment; additionally, complications related to thermal damage (in the form of skin burns), infection and nerve injury did not occur in any patients. Other recent and mostly retrospective studies have shown the same results, with a relatively low rate of complications [11, 15, 16, 21, 22]. Similarly, the results of our study also indicate that MWA is a safe and efficient approach, with only three minor complications related to thermal injury that caused myofasciitis and affected wound healing in the entire study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Recently, Cheng et al [34] have shown that ultrasound-guided percutaneous MWA has the advantages of being a real-time, convenient, lower-cost and nonradiative treatment; additionally, complications related to thermal damage (in the form of skin burns), infection and nerve injury did not occur in any patients. Other recent and mostly retrospective studies have shown the same results, with a relatively low rate of complications [11, 15, 16, 21, 22]. Similarly, the results of our study also indicate that MWA is a safe and efficient approach, with only three minor complications related to thermal injury that caused myofasciitis and affected wound healing in the entire study.…”
Section: Discussionsupporting
confidence: 89%
“…Percutaneous MWA techniques have been used for the treatment of patients with several benign and metastatic bone lesions, and major complications are infrequent [6, 1517, 21, 22, 27, 33, 34]. Kastler et al [27] reported the successful treatment of spinal metastases with MWA, without any major complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,27,28 Khan et al 27 reported a dramatic reduction of the pain score after percutaneous MWA and cementoplasty in 84 thoracolumbar sites of painful spinal metastases and myeloma. Liu et al 14,15 demonstrated that MWA combined with open decompression surgery for patients with breast cancer-derived thoracic metastatic tumors is an effective treatment that maintains or improves functional outcomes better than open surgery. However, Kastler et al 28 did not use cement augmentation combined with MWA and reported moderate pain improvement.…”
Section: Discussionmentioning
confidence: 99%
“…MWA with open decompression therapy in 23 patients with breast cancer-derived thoracic metastases showed that 78.3% of them improved their score. 15 However, these two findings were from retrospective studies without a control group and a limited sample size. Zhang et al 16 showed that applying MWA in 69 patients with pathological spinal fractures had more advantages in alleviating pain and improving the quality of life when combined with decompression and pedicle screw fixation than not performing MWA.…”
Section: Introductionmentioning
confidence: 98%